Lithospheric transdimensional ambient-noise tomography of W-Europe: implications for crustal-scale geometry of the W-Alps. Issue 2 (24th December 2021) - Nouibat, A; Stehly, L; Paul, A; Schwartz, S; Bodin, T; Dumont, T; Rolland, Y; Brossier, R; ,
SUMMARY: A full understanding of the dynamics of mountain ranges such as the Alps requires the integration of available geological and geophysical knowledge into a lithospheric-scale 3-D geological model. As a first stage in the construction of this geo-model, we derive a new 3-D shear wave velocity model of the Alpine region, with a spatial resolution of a few tens of kilometres, making it possible to compare with geological maps. We use four years of continuous vertical-component seismic noise records to compute noise correlations between more than 950 permanent broad-band stations complemented by ∼600 temporary stations from the AlpArray sea-land seismic network and the Cifalps and EASI linear arrays. A specific pre-processing is applied to records of ocean–bottom seismometers in the Liguro-Provençal basin to clean them from instrumental and oceanic noises. We first perform a 2-D transdimensional inversion of the traveltimes of Rayleigh waves to compute group-velocity maps from 4 to 150 s . The data noise level treated as an unknown parameter is determined with a Hierarchical Bayes method. A Fast Marching Eikonal solver is used to update ray path geometries during the inversion. We use next the group-velocity maps and their uncertainties to derive a 3-D probabilistic Vs model. The probability distributions of Vs at depth and the probability of presence of an interface are estimated at each location by exploring a set of 130 million synthetic four-layer 1-D Vs models. The obtained probabilistic model is refined using a linearized inversion. Throughout the inversion for Vs, we include the water column where necessary. Our Vs model highlights strong along-strike changes of the lithospheric structure, particularly in the subduction complex between the European and Adriatic plates. In the South-Western Alps, our model confirms the existence of a low-velocity structure at 50-80 km depth in the continuation of the European continental crust beneath the subduction wedge. This deep low-velocity anomaly progressively disappears towards the North-Western and Central Alps. The European crust includes lower crustal low-velocity zones and a Moho jump of 8-12 km beneath the western boundary of the External Crystalline Massifs of the North-Western Alps. The striking fit between our Vs model and the receiver function migrated depth section along the Cifalps profile documents the reliability of the Vs model. In light of this reliability and with the aim to building a 3-D geological model, we re-examine the geological structures highlighted along the Cifalps profile.